2021
DOI: 10.3389/fdgth.2021.758031
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Cognitive Performance on Mobile Devices Is Sensitive to Mild Cognitive Impairment: Results From the Einstein Aging Study

Abstract: Background and Objective: Within-person variability in cognitive performance has emerged as a promising indicator of cognitive health with potential to distinguish normative and pathological cognitive aging. We use a smartphone-based digital health approach with ecological momentary assessments (EMA) to examine differences in variability in performance among older adults with mild cognitive impairment (MCI) and those who were cognitively unimpaired (CU).Method: A sample of 311 systematically recruited, communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 67 publications
(100 reference statements)
5
43
0
Order By: Relevance
“…Also, consistently across the two tasks, individuals with more years of education exhibited less variability. Paired with our previous findings that intra-individual variation in performance predicts MCI status, this may suggest that day-to-day variation reflects individual differences in cognitive reserve ( Cerino et al, 2021 ).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Also, consistently across the two tasks, individuals with more years of education exhibited less variability. Paired with our previous findings that intra-individual variation in performance predicts MCI status, this may suggest that day-to-day variation reflects individual differences in cognitive reserve ( Cerino et al, 2021 ).…”
Section: Discussionsupporting
confidence: 65%
“…While the primary aim of BDEM is to disentangle learning features from peak performance (with the goal of modeling asymptotic change over time), each model parameter may also be of interest for understanding the dynamics of cognitive change. For this reason, we also quantify individual differences, in a multilevel framework, not only in terms of peak performance and changes therein, but also for example in terms of learning rate, and intra-individual variability in performance, and test whether these are linked to cognitive aging ( Lövdén et al, 2007 ) or MCI status ( Cerino et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Table S5: Diagnostic performance of digital cognitive biomarkers for cognitive impairments (CI). Table S6: Quality assessment based on The Newcastle–Ottawa Scale (NOS) [ 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 ]. Figure S1: Between-group mean difference in cognitive outcomes measured by computerized tests in mild cognitive impairments (MCI) and normal controls.…”
mentioning
confidence: 99%
“…Of note, Patient A exhibits greater session-to-session, intra-individual variation than Patient B. Inconsistency in speeded performance in other populations (e.g., older adults) has been identified as a risk factor for cognitive impairment ( 31 33 ). Recently, in a study using M2C2, we found that older adults with mild cognitive impairment exhibit significantly greater session-to-session and day-to-day variation in Symbol Search task performance than cognitively-unimpaired older adults ( 34 ). A primary aim of the MNCH project is to determine if RT inconsistency is a clinically-relevant marker of cognitive impairment following concussion.…”
Section: Performance-based Ambulatory Cognitive Assessmentsmentioning
confidence: 97%